Inovasi Pelayanan Warung Samsat Sore dan Malam (SAMSORELAM) terhadap Pembayaran Pajak Kendaraan Bermotor di SAMSAT Martapura - Nurjanah, Siti; Purboningsih, Dewi (Journal of Social and Policy Issues, 2024)
The SAMSAT Martapura Regional Revenue Service Unit has carried out a service innovation program in the form of Warung SAMSORELAM as a solution to solving public problems in the form of public demands that there is not enough time to pay motor vehicle tax during working hours. The aim of this research is to determine Warung SAMSORELAM Service Innovation, as well as supporting and inhibiting factors for Warung SAMSORELAM Service Innovation. A descriptive qualitative approach was employed as the research methodology in this study. The research focus is based on innovation theory according to Rogers with indicators namely relative advantage, compatibility, complexity, triability and observability. The results of the research show that Warung SAMSORELAM's service innovation for motor vehicle tax payments has gone well. Relative advantage can be seen from the time the service is carried out outside working hours. Compatibility is seen only in the form of mobile Samsat cars and there are no café facilities. Complexity shows that there is no complexity in the implementation process. Triability can be seen from the positive response from the community. Observability can be seen from the ease of observing both the procedures and service mechanisms which are not complicated and the requirements are easy for the community to fulfill. The supporting factors for Warung SAMSORELAM's service innovation are strategic location and additional service time outside working hours. Meanwhile, the inhibiting factors for Warung SAMSORELAM's service innovation are that the network can be disrupted and the facilities are inadequate.